2017
DOI: 10.1111/2041-210x.12709
|View full text |Cite
|
Sign up to set email alerts
|

An environmental DNA‐based method for monitoring spawning activity: a case study, using the endangered Macquarie perch (Macquaria australasica)

Abstract: Summary1. Determining the timing and location of reproductive events is critical for efficient management of species. However, methods currently used for aquatic species are costly, time intensive, biased and often require destructive or injurious sampling. Hence, developing a non-invasive sampling method to accurately determine the timing and location of reproduction for aquatic species would be extremely valuable. 2. We conducted an experimental and field study to determine the influence of spawning, and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
181
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(195 citation statements)
references
References 54 publications
9
181
1
Order By: Relevance
“…; Bylemans et al. ). Furthermore, others have shown that persistence rates differ among streams of various sizes and characteristics (Wilcox et al.…”
Section: Discussionmentioning
confidence: 97%
“…; Bylemans et al. ). Furthermore, others have shown that persistence rates differ among streams of various sizes and characteristics (Wilcox et al.…”
Section: Discussionmentioning
confidence: 97%
“…A range of sampling approaches has previously been employed which have varied in sample size from, for example, c. 1,000 × 2 L samples from a canal and waterway system (Jerde, Mahon, Chadderton, & Lodge, 2011), to 5 × 15 ml samples from a sea pen (volume of 4 million liters) within a harbor (Foote et al, 2012). Similarly, it has been confirmed that spawning events are characterized by a higher relative abundance of eDNA (Bylemans et al, 2017) making the spawning season an ideal time to utilize eDNA for biomonitoring within lotic systems. Quantifying eDNA to estimate the biomass of a target species in running water is invariably complicated and requires the consideration of many variables including eDNA shedding and degradation rate at time of sampling; water temperature; pH; salinity; flow rate; water volume; hydro-morphology; and the dendritic organization of the habitat (Rees et al, 2014;Roussel, Paillisson, Tréguier, & Petit, 2015;Thomsen et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…A quantitative polymerase chain reaction (qPCR) assay targeting crucian carp was also published in the context of early warning invasion monitoring for fish species that may arrive in Canada (Roy, Belliveau, Mandrak, & Gagné, ), but was only tested on tissue‐derived DNA. Of equal importance to invasion monitoring, eDNA analysis has enhanced surveys for threatened and endangered freshwater fish (Bylemans et al., ; Piggott, ; Schmelzle & Kinziger, ; Sigsgaard et al., ).…”
Section: Introductionmentioning
confidence: 99%